High-Flow Oxygen Therapy After Noninvasive Ventilation Interruption in Patients Recovering From Hypercapnic Acute Respiratory Failure: A Physiological Crossover Trial. Issue 6 (June 2019) - Longhini, Federico; Pisani, Lara; Lungu, Ramona; Comellini, Vittoria; Bruni, Andrea; Garofalo, Eugenio; Laura Vega, Maria; Cammarota, Gianmaria; Nava, Stefano; Navalesi, Paolo
Abstract : Objectives: Assessing gas exchange, diaphragm function, respiratory rate, and patient comfort during high-flow oxygen therapy and standard oxygen at the time of noninvasive ventilation discontinuation. Design: Randomized crossover physiologic study. Setting: Two ICUs. Patients: Thirty chronic obstructive pulmonary disease patients with hypercapnic acute respiratory failure receiving noninvasive ventilation greater than 24 hours. Interventions: All patients underwent five 30-minute trials, the first, third, and fifth trial in noninvasive ventilation, whereas the second and fourth were randomly conducted with either standard oxygen and high-flow oxygen therapy. Measurements and Main Results: Diaphragm displacement and thickening fraction were determined by sonographic evaluation at the end of each trial. Arterial blood gases, respiratory rate, and patient comfort were also assessed. PaCO2 ( p = 0.153) and pH ( p = 0.114) were not different among trials, while PaO2 was greater in noninvasive ventilation than with both standard oxygen ( p ⩽ 0.005) and high-flow oxygen therapy ( p ⩽ 0.001). The diaphragm displacement was no different among trials ( p = 0.875), while its thickening fraction was greater with standard oxygen, compared with high-flow oxygen therapy and all noninvasive ventilation trials ( p < 0.001 for all comparisons), without differences between high-flow oxygen therapy and noninvasive ventilation. Respiratory rate also increased with standard oxygen, compared with both high-flow oxygen therapy ( p < 0.001) and noninvasive ventilation ( p < 0.01). High-flow oxygen therapy improved comfort, compared with standard oxygen ( p = 0.004) and noninvasive ventilation ( p < 0.001). Conclusions: At the time of noninvasive ventilation interruption, PaCO2 and diaphragm displacement remained unchanged regardless of the modality of oxygen administration. However, although standard oxygen resulted in a remarkable increase in diaphragm thickening fraction, high-flow oxygen therapy allowed maintaining it unchanged, while improving patient comfort.